Identification of Salmonella sp. bacteria, antibiotic tetrasicline in cultivated silkworms using chicken manure media - Umidayati Umidayati (Sains Akuakultur Tropis : Indonesian Journal of Tropical Aquaculture, 2022)
ABSTRACT[Identification of Salmonella Sp.  Bacteria, Antibiotic Tetrasicline in Cultivated Silkworms using Chicken Manure Media]Sustainability of farming activities is determined by the use of materials that are free from pathogens, residues of antibiotics and other chemicals. Prevention of pathogenic microorganisms can be done through the use of disease-free seed with a certificate Specific Pathogen Free guided by way of Good Aquaculture (CBIB). This study uses a completely randomized design (CRD) with 2 treatment (fermentation methods and non-fermented) and three replications. The identification results on the silkworms with fermentation methods and non-fermenting bacteria positive for Salmonella sp positive and tetracycline antibiotic residues (> 32 ppb) in the silkworm cultivation. Productivity silkworms in the fermentation medium are higher than in non-fermented in the amount of 267.91 ± 113.18 g / m2 / cycle and for non-fermented 201.89 ± 16,85g / m2 / cycle. Absolute growth fermentation medium peak at 30.92 ± 2.9 g / m2 and non-fermented 9.12 ± 1.99 g / m2. KEYWORDS: Antibiotics, silkworms, chicken manure, Salmonella sp.